HIV/AIDS e conjugalidade: a experiência de pessoas em relacionamentos afetivo-sexuais sorodiscordantes. - Lourenço, Gilclécia Oliveira (2018)
This study planned to understand the conjugality experience of people with mixed HIV status for HIV/AIDS. It is very important to expand knowledge of sexual-affective relational possibilities affected by the contamination with HIV/AIDS to reflect about intake practices that consider the context and demands of people living with this virus. In this sense, this study is categorized as a qualitative research in which 16 individuals were separately interviewed, 05 of them were HIV-negative and the remaining 11 were HIV-positive, all in serodiscordant relationships. In addition to the semi-structured interview, we also used a Field Journal where several experiences, observations and reflections built along the process of data production were recorded. As an analytical strategy, we used the discursive analysis inspired on Foucault. Reports of the interviewees point to a conjugality experience marked by stigmas, prejudices and conflicts on the understanding of the virus in the lives of the couples and an ongoing surveillance in their daily lives. In serodiscordant couples, sexual relations affected by discourses of risk and prevention, are experienced with fear, doubt and insecurity. Moreover, we noticed that HIV infection comprises tensions and experiences in the dynamics of the couples that cannot be reduced to aspects of sexuality, prevention and risk. The experience of serodiscordant conjugality has complex effects on the couples’ daily lives and involves the development of different strategies required for the construction and/or maintenance of the sexual-affective relationship. It is concluded that the AIDS discourse acts on the individual, producing means to relate, be a couple and be serodiscordant, in a subjectivation process determined by political, regulatory and cultural strategies. However, the experience of serodiscordant conjugality is defined as a complex phenomenon that cannot be explained by causal and simplistic explanations. The individual presented here is active in its subjectivation process, creating means of resistance and subversion that emphasize the disciplinary power of the AIDS discourse.